Anal HPV shedding assessed by self-sampling and multiplex real-time PCR among men who have sex with men in N’Djamena, Chad: a feasibility and acceptability study - Donato Koyalta; Zita Aleyo Nodjikouambaye; Jonathan Muwonga Tukisadila; Hachim Djamal Abdoulaye Bargo; Suitombaye Noubaramadji Yamti; Amine Akouya; Ralph-Sydney Mboumba Bouassa; Laurent Belec (PLoS ONE, 2026)
Background High-risk (HR) human papillomavirus (HPV) infection remains a great concern in sub-Saharan Africa in men who have sex with men (MSM). The prevalence of anal shedding of HPV and associated risk factors was estimated for the first time in a cross-sectional observational study covering MSM living in N’Djamena, the capital city of Chad. Methods MSM were recruited from the community in 21 sites in neighborhoods of 5 districts randomly selected in N’Djamena by respondent-driven sampling (RDS) method. Anal Collector V-Veil UP2™ device was used for anal canal self-sampling. Manual silica-extracted DNA was subjected for HPV detection and genotyping using BMRT Human Papillomavirus Genotyping Real Time PCR assay (Jiangsu Bioperfectus Technologies Co., Ltd., Taizhou, China). HIV serostatus was assessed using two rapid tests in series. Results A total of 70 MSM (mean age: 29.9 years; range, 18–50) were included. The overall acceptability to practice veil-based anal self-sampling was 95.9%. The usability of the veil collector device was high (92.3%), with easy understandable instructions for use and correct placement in the anal canal. Satisfaction questionnaire reported high overall feeling, intimacy respect and lack of shame. The majority of MSM (44/70, 62.8%) showed anal shedding of HPV DNA, with HR-HPV frequently detected (38,70, 54.3%), including HPV-33 (30/70, 42.9%) HPV-68 (16/70, 22.9%), HPV-18 (4/70, 5.7%), HPV-35 (3/70, 4.3%), HPV-58 (2/70, 2.9%), and HPV-45 (1/70, 1.4%). The distribution of genotypes in HR-HPV DNA-positive MSM revealed that HPV-33 (30/70; 42.9%) was the predominant genotype, followed by the HPV-68 (16/70; 22.9%), HPV-18 (4/70; 5.7%), HPV-35 (3/70; 4.3%), HPV-58 (2/70; 2.9%), and HPV-45, HPV-51 and HPV-56 (each type, 1/70;1.4%). Among all HPV detected, only 42 HPV (36.8%) were covered by Gardasil-9 ® vaccine, including the HR-HPV-33, −18, −58 and −45, and the low risk-HPV-6 (5.7%) and HPV-11 (1.4%). The majority of detected HPV were non-covered by Gardasil-9 ® vaccine (63.1%). Overall HIV prevalence was 5.7%. Conclusions Taken together, these observations point the MSM population in N’Djamena as a very particular core group of HIV and HPV transmission. HIV prevalence was higher than that of general adult population, but limited to only one MSM of twenty. The RDS method of recruitment allowed to include MSM likely belonging to the same sexual network of HPV transmission leading to the selection of an atypical and specific profile of anal HPV distribution. The potential efficacy of HPV prophylactic vaccination in this population can be estimated at relatively weak.